Human papillomavirus infection and use of oral contraceptives. - Green, J; Berrington de Gonzalez, A; Smith, J; Franceschi, S; Appleby, P; Plummer, M; Beral, V (2003)
Human papillomavirus (HPV) infection is thought to be a necessary but not sufficient cause of most cases of cervical cancer. Since oral contraceptive use for long durations is associated with an increased risk of cervical cancer, it is important to know whether HPV infection is more common in oral contraceptive users. We present a systematic review of 19 epidemiological studies of the risk of genital HPV infection and oral contraceptive use. There was no evidence for a strong positive or negative association between HPV positivity and ever use or long duration use of oral contraceptives. The limited data available, the presence of heterogeneity between studies and the possibility of bias and confounding mean, however, that these results must be interpreted cautiously. Further studies are needed to confirm these findings and to investigate possible relations between oral contraceptive use and the persistence and detectability of cervical HPV infection.